ANALYSIS OF CONSUMER’S CONFUSION IN SELECTING THE DIFFERENT TYPES OF MINERAL WATER IN MANADO - Suban, Gabriela T.; Tumewu, Ferdinand (FEB Universitas Sam Ratulangi Manado, 2019)
Consumer Confusion is a state of mind that leads to consumers making imperfect purchasing decisions or lacking confidence in the correctness of their purchasing decisions, also consumer confusion can affect by so many factors also Consumer confusion can be defined as a condition that individuals may be prone to and which causes them to act differently and/ or affects their decisions making behavior. The aim of this study is to analyze the consumer confusion in selecting the different typs of mineral water in Manado and also to analyze what cause consumer confusion. In order to achieve these objectives the researcher got information from 15 respondents using qualitative study which is in-depth interview and uses purposive sampling. The results showed that consumer confusion occurs many times among the respondents, and consumer confusion occurs also when people had faces so many different types or different brand of mineral water at the same time, especially when the product that they have been looking for was sold out or did not sell at the supermarket and they have to choose and select another brand of mineral water, and when they saw many different brand of mineral water it can makes the confused. The recommendation, this research can give knowledge about the consumer confusion and can explore about the experience when gets confused when selecting the different types of mineral water.Keywords: consumer confusion, types of mineral water